2003
DOI: 10.1038/emm.2003.41
|View full text |Cite
|
Sign up to set email alerts
|

Activation of calcium signaling by hepatitis B virus-X protein in liver cells

Abstract: Abbreviations: CREB, cyclic AMP response element binding protein; DMSO, dimethylsulfoxide; ECL, enhanced chemiluminescence. EDTA, ethylenediaminetetraacetic acid; EGTA, ethylene-bis (oxyethylenenitrilo)tetraacetic acid; HCC, hepatocellular carcinoma; IP3, inositol-3-phosphate; MAPK (Erk), mitogen activated protein kinase; NF-AT, nuclear factor of activated T cells; PCNA, proliferative cell nuclear antigen; PI3K, phosphatidylinositol-3-kinase; PIP3, phosphatidylinositol-3-phosphate; SAPK/JNK, stress activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…Similarly, another group reported increased phosphorylation of Raf, ERK, and JNK leading to increased activation of c-jun and AP-1; these events appear to be mediated by increased cytosolic calciums level resulting from HBx transfection. 112 These data seem to corroborate the conclusions of Schneider and Benn that both Ras-MEKK-JNK and Ras-Raf-ERK pathways are involved in AP-1 activation. 102 Importantly, these in vitro findings are supported by in vivo experiments using a mouse model.…”
Section: Ras-raf-mapksupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly, another group reported increased phosphorylation of Raf, ERK, and JNK leading to increased activation of c-jun and AP-1; these events appear to be mediated by increased cytosolic calciums level resulting from HBx transfection. 112 These data seem to corroborate the conclusions of Schneider and Benn that both Ras-MEKK-JNK and Ras-Raf-ERK pathways are involved in AP-1 activation. 102 Importantly, these in vitro findings are supported by in vivo experiments using a mouse model.…”
Section: Ras-raf-mapksupporting
confidence: 84%
“…107 They later demonstrate that the c-fos component of AP-1 was activated through Ras-Raf-ERK signaling, while the c-jun component was stimulated through the Ras-MEKK-JNK cascade. 112 This would appear to be at odds with the findings of Natoli et al as their study emphasized the requirement of Raf in c-jun activation. 110 Likewise, an earlier study reported activation of c-jun by MAPK/ ERK.…”
Section: Ras-raf-mapkmentioning
confidence: 94%
See 1 more Smart Citation
“…There is evidence that HBx is an essential viral protein with pleiotropic activity that might act directly or indirectly on development of hepatocellular carcinoma during chronic hepadnavirus infection [4,5] . Over-expression of HBx induces transformation of some cell types [6] .Additionally, it has been reported that HBx is involved in the arrest of cell cycle progression and the modulation of apoptosis [7,8] . HBx protein also interacts with the tumor suppressor p53, resulting in a loss of its function [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of cellular MTT reduction was carried out essentially as described (Kim et al, 2003a;Oh et al, 2003). Following the appropriate incubation time with peptide, 10 µl of MTT solution (5 mg/ml of MTT in phosphate-buffered saline [PBS]) was added to a final concentration of 0.5 mg/ml, and incubation was continued for 2.5 h for MTT formazan exocytosis assay, and 4 h for quantitation assay, respectively.…”
Section: Mtt Reduction and Mtt Formazan Exocytosismentioning
confidence: 99%